Masyarakat Sigap dan Tanggap Covid-19: Pengabdian Kepada Masyarakat di Kampung Cikarang, Desa Kadu Hejo, Kecamatan Pulosari, Pandeglang - Mualwi Widiatmoko; Aam Munjiah; Mina Miftahul Falah; Wahyuni Widiyanti Fazrin; Amelia Ayu Pratiwi; Mila Rosmila; Misjaya Misjaya (Universitas Mathla'ul Anwar Banten, 2020)
COMMUNITIES WITH RESPONSE AND RESPONSE TO COVID-19: COMMUNITY SERVICE IN CIKARANG VILLAGE, KADU HEJO VILLAGE, PULOSARI DISTRICT, PANDEGLANG. This community service activity provided services and assistance to children in rural areas during the Covid-19 Pandemic which hit the whole world and Indonesia was also affected, from the economic sector to education. For education itself, the government has agreed to study at home or online. By using various strategies so that the nation's successors can still learn even though not face to face. Lecturers and students of Unma Banten guidance and counseling had the opportunity to go to the field by prioritizing health protocols and providing disaster counseling services at Cikarang Village, Kadu Hejo Village, Pulosari District, Pandeglang.